(untitled) (ІННОВАЦІЙНА ЕКОНОМІКА, 2019)
Сосновська О.О. МЕТОДОЛОГІЯ ПОБУДОВИ ФІНАНСОВОЇ АРХІТЕКТОНІКИ ПІДПРИЄМСТВ ЗВ’ЯЗКУ Мета. Визначення методологічних елементів фінансової архітектоніки підприємств зв’язку, органічне поєднання та ідентифікація взаємодії яких буде сприяти підвищенню рівня фінансової безпеки даних підприємств. Методика дослідження. У даному дослідженні використовувались наступні методи: діалектики та наукової абстракції – при визначенні сутності фінансової архітектоніки підприємств зв’язку; аналізу та синтезу – при визначенні структурних елементів побудови фінансової архітектоніки підприємств. При створенні методологічного алгоритму побудови фінансової архітектоніки підприємств зв’язку використано методичний підхід, який враховує різноманіття фінансово-управлінських процесів в їх взаємозв’язку та взаємозалежності для підвищення загального рівня фінансової безпеки. Результати дослідження. Обґрунтовано наявність проблемних аспектів у існуючих підходах до визначення фінансової архітектоніки, взаємозв’язку та взаємодії її структурних складових, закономірностях побудови економічних та фінансових елементів в цілісну систему. Визначено сутність фінансової архітектоніки підприємства як сукупності взаємозалежних та взаємопов’язаних елементів фінансового середовища підприємств зв’язку, логічна структуризація яких буде сприяти підвищенню ефективності їх фінансової діяльності у контексті розробки та реалізації управлінських рішень щодо оптимізації фінансових ризиків для підвищення рівня фінансової безпеки. Запропоновано методологічний алгоритм побудови фінансової архітектоніки підприємств зв’язку як стратегічного напряму підвищення рівня їх фінансової безпеки в умовах економічної нестабільності та фінансових ризиків. Сформовано методологічну основу побудови фінансової архітектоніки підприємств зв’язку як низка принципів, які забезпечують логічну структуризацію складових фінансової діяльності підприємств зв’язку, оптимальне їх співвідношення та взаємозв’язки, дають змогу врахувати взаємозалежність із домінуючими детермінантами мікроекономічного та макроекономічного середовища і через реалізацію фінансових управлінських рішень щодо оптимізації фінансових ризиків підприємств зв’язку дозволяють ефективно впливати на весь відтворювальний процес. Визначено основні етапи побудови фінансової архітектоніки підприємств зв’язку для прийняття та реалізації обґрунтованих управлінських рішень щодо оптимізації фінансових ризиків даних підприємств. Наукова новизна результатів дослідження. Обґрунтувано теоретично-методологічні підходи, які в сукупності вирішують важливу наукову проблему щодо визначення поняття фінансової архітектоніки підприємств зв’язку, яке, на відміну від існуючих, охоплює логічну структуризацію всіх складових фінансової діяльності підприємств зв’язку, оптимальне їх співвідношення та взаємозв’язки. Розроблено методологічний алгоритм побудови фінансової архітектоніки підприємств зв’язку, який поєднує усі необхідні складові елементи з урахуванням їх взаємозалежності та взаємодії, а також визначає основні шляхи та етапи досягнення фінансової безпеки підприємств відповідної галузі. Практична значущість результатів дослідження. Отримано можливість використання розробленого методологічного алгоритму побудови фінансової архітектоніки на підприємствах зв’язку, що дозволить реальним підприємствам даної галузі протистояти виникненню нових ризиків та загроз фінансового характеру як результату пошуку та впровадження нових комплексних адаптивних рішень з управління їх фінансовими ресурсами, а також забезпечити стійкі параметри функціонування. Ключові слова: фінансова архітектура; фінансова архітектоніка; структурні елементи; підприємства зв’язку; фінансова безпека; фінансова діяльність. Сосновская О.А. МЕТОДОЛОГИЯ ПОСТРОЕНИЯ ФИНАНСОВОЙ АРХИТЕКТОНИКИ ПРЕДПРИЯТИЙ СВЯЗИ Цель. Целью статьи является определение методологических элементов финансовой архитектоники предприятий связи, органическое сочетание и идентификация взаимодействия которых будет способствовать повышению уровня финансовой безопасности данных предприятий. Методика исследования. В данном исследовании использовались следующие методы: при определении сущности финансовой архитектоники предприятий связи использованы методы диалектики и научной абстракции. Структурные элементы построения финансовой архитектоники предприятий связи определены с помощью использования методов анализа и синтеза. При создании методологического алгоритма построения финансовой архитектоники предприятий связи использован методический подход, учитывающий многообразие финансово-управленческих процессов в их взаимосвязи и взаимозависимости для повышения общего уровня финансовой безопасности. Результаты исследования. Обосновано наличие проблемных аспектов в существующих подходах к определению финансовой архитектоники, взаимосвязи и взаимодействия ее структурных составляющих, закономерностях построения экономических и финансовых элементов в целостную систему. Определена сущность финансовой архитектоники предприятия как совокупности взаимозависимых и взаимосвязанных элементов финансовой среды предприятий связи, логическая структуризация которых будет способствовать повышению эффективности их финансовой деятельности в контексте разработки и реализации управленческих решений по оптимизации финансовых рисков для повышения уровня финансовой безопасности. Предложен методологический алгоритм построения финансовой архитектоники предприятий связи в качестве стратегического направления повышения уровня их финансовой безопасности в условиях экономической нестабильности и финансовых рисков. Сформирована методологическая основа построения финансовой архитектоники предприятий связи как ряд принципов, которые обеспечивают логическую структуризацию составляющих финансовой деятельности предприятий связи. Оптимальное соотношение и взаимосвязи данных принципов позволяют учесть взаимозависимость с доминирующими детерминантами микроэкономической и макроэкономической среды и, через реализацию финансовых управленческих решений по оптимизации финансовых рисков предприятий связи, позволяют эффективно влиять на весь воспроизводственный процесс. Определены основные этапы построения финансовой архитектоники предприятий связи для принятия и реализации обоснованных управленческих решений по оптимизации финансовых рисков данных предприятий. Научная новизна результатов исследования. Обоснованы теоретико-методологические подходы, которые в совокупности решают важную научную проблему по обоснованию определения понятия финансовой архитектоники предприятий связи, которое, в отличие от существующих, охватывает логическую структуризацию всех составляющих финансовой деятельности предприятий связи, оптимальное их соотношение и взаимосвязи. Разработан методологический алгоритм построения финансовой архитектоники предприятий связи, который сочетает все необходимые составляющие элементы с учетом их взаимозависимости и взаимодействия, а также определяет основные пути и этапы достижения финансовой безопасности предприятий соответствующей отрасли. Практическая значимость результатов исследования. Получена возможность использования разработанного методологического алгоритма построения финансовой архитектоники на предприятиях связи, что позволит реальным предприятиям данной отрасли противостоять возникновению новых рисков и угроз финансового характера как результата поиска и внедрения новых комплексных адаптивных решений по управлению их финансовыми ресурсами, а также обеспечит устойчивые параметры их функционирования. Ключевые слова: финансовая архитектура, финансовая архитектоника, структурные элементы, предприятия связи, финансовая безопасность, финансовая деятельность. Sosnovska О.О. METHODOLOGY OF CONSTRUCTION OF THE FINANCIAL ARCHITECTONICS OF COMMUNICATION ENTERPRISES Purpose. The purpose of the article is to identify the methodological elements of the financial architectonics business communications, the organic combination and the identification of their interaction will contribute to increasing the financial security of these enterprises. Methodology of research. The following methods were used in this study: methods of dialectics and scientific abstraction were used to determine the essence of the financial architectonics business communications. Structural elements of construction of the financial architectonics business communications were discovered using the methods of analysis and synthesis. When creating a methodological algorithm for constructing the financial architectonics business communications, a methodical approach is used which takes into account the diversity of financial and managerial processes in their interconnection and interdependence in order to increase the overall level of financial security. Findings. The existence of problem aspects in existing approaches to the definition of the financial architectonic, the interconnection and interaction of its structural components, the laws of constructing economic and financial elements into a coherent system is substantiated. The essence of the financial architectonics of the enterprise as a set of interrelated and interrelated elements of the financial environment of the business communications is determined, the logical structuring of which will help to increase the efficiency of their financial activity in the context of development and implementation of managerial decisions on optimization of financial risks to increase the level of financial security. The methodological algorithm of the financial architectonics business communications construction as a strategic direction of their financial safety level increase in conditions of economic instability and financial risks is offered. The methodological basis for the financial architectonics business communications constructing as a set of principles that provide logical structuring of the components of financial activity of communication enterprises is formed, their optimum relations and interconnections allow taking into account the interdependence with the dominant determinants of the microeconomic and macroeconomic environment and through the implementation of financial management decisions to optimize the financial risks of communications companies can effectively affect the entire reproduction process. The basic stages of construction of financial architecture of communication companies for the adoption and implementation of sound management decisions on optimization of financial risks of these enterprises are determined. Originality. The scientific novelty of the results of this study is to substantiate theoretical and methodological approaches, which collectively solve an important scientific problem regarding a well-defined definition of the concept of financial architecture of communications enterprises. It, in contrast to the existing ones, encompasses the logical structuring of all components of the financial activity of communications companies, their optimal relationships and interconnections. The developed methodological algorithm for the financial architectonics business communications constructing combines all the necessary constituent elements taking into account their interdependence and interaction, defines the main ways and stages of achieving the financial security of enterprises in the industry. Practical value. The practical significance of the research results obtained is the possibility of using the developed methodological algorithm for the financial architectonics business communications constructing. This will allow real enterprises in this industry to withstand the emergence of new risks and threats of a financial nature as a result of the search and introduction of new integrated, adaptive solutions for managing their financial resources and ensure stable operation parameters. Key words: financial architecture; financial architectonics; structural elements; business communications; financial security; financial activities.